Implementasi Trilogi Ki Hadjar Dewantara di SD Taman Muda Jetis Yogyakarta - Nugroho, Wahyu (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2018)
The problems of elementary school students are very worrying. Juvenile delinquency, acts of violence, and sexual harassment can not be separated from the responsibilities of teachers. A teacher has a role to teach, nurture, and control the character of the student optimally so as to create a virtuous generation. SD Taman Muda under the auspices of the Majelis Luhur Tamansiswa Foundation is an educational institution in Yogyakarta that holds firmly to the Trilogy of Ki Hajar Dewantara: 1) Ing ngarsa sung tuladha; 2) Ing madya mangun karsa; 3) Tutwuri handayani. This trilogy is expected to be able to answer the challenge of education to form students with character. The purpose of this lesson is to analyze the low grade teachers in elementary schools applying the Trilogy Ki Hadjar Dewantara to develop the character of grade 1, 2, and 3 students. The research method used qualitative approach with descriptive type. Data obtained through observation, interviews, and documentation and supporting literature. Data analysis using Miles and Huberman model. Technique of examination of data validity by triangulation of source and technique. The results showed that the role of teachers in applying the trilogy Ki Hadjar Dewantara by being exemplary, motivating and encouraging students in accordance with the natural development.